2012
DOI: 10.1093/rpd/ncs031
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray rejection, or detection, with gadolinium as a converter

Abstract: Gadolinium is a competent neutron conversion material for neutron detection due to its extremely high neutron capture cross section. It differs from the other neutron reactive materials by emitting large amounts of low-energy electrons for the consequent signal generation in a detector. Such low-energy electrons, though abundant, are prone to be contaminated by internal and/or external gamma rays, such as the activated 43.0 keV K-X rays, given the high atomic number of gadolinium. While the 43.0 keV K-X ray ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…These phenomena, however, boost the c-ray detection efficiency when Gd is combined with GaN or other semiconducting materials. 98,99 A rare-earth-doped GaN thin film might lead to significant improvements in device performance in sensor applications; GaN is potentially neutron sensitive when doped with Gd. 100,101 Melton et al 102 found that the carrier concentration in Gd-doped GaN increases as a result of the Gd doping.…”
Section: Neutron Detectionmentioning
confidence: 99%
“…These phenomena, however, boost the c-ray detection efficiency when Gd is combined with GaN or other semiconducting materials. 98,99 A rare-earth-doped GaN thin film might lead to significant improvements in device performance in sensor applications; GaN is potentially neutron sensitive when doped with Gd. 100,101 Melton et al 102 found that the carrier concentration in Gd-doped GaN increases as a result of the Gd doping.…”
Section: Neutron Detectionmentioning
confidence: 99%
“…6 A). All further experiments were therefore carried out using a 10 μm Gd layer, which was close to the 12 μm predicted previously for high efficiency [ 16 ].…”
Section: Resultsmentioning
confidence: 78%
“…This situation is exacerbated when compared with low natural neutron background fluence. There are two sources contributing to γ-ray background: external γ-rays accompanying 252 Cf and internal prompt γ-rays [ 16 ] (Eqs 1 and 2 ) due to Gd's ( Z = 64) high probability of interaction that produces moderate energy electrons by Compton, photoelectric and electron–positron pair processes [ 17 ]. These factors make it easy to record false positives while detecting SNMs, since an electron from γ-interaction is not easily distinguished from ICEs.…”
Section: Resultsmentioning
confidence: 99%
“…Gd [67]. This explains the extra bump around relatively high energies in the simulated neutron spectrum with updated Geant4.…”
Section: Modeling Gadolinium Neutron Capture Gamma Emissionmentioning
confidence: 75%
“…The simulated individual gamma emission spectrum from Geant4.9.4.p04 (photon evaporation model) is shown in red, and the individual gamma spectrum from Geant4.9.5.p01 (G4NDL) is shown in blue. The measured individual gamma spectrum from 155 Gd and 157 Gd together [66] is shown in black solid line, and the spectrum measured from natural Gd [67] is shown in black dashed line. G4NDL agrees with the measured spectra much better than photon evaporation model at high energy.…”
Section: Modeling Gadolinium Neutron Capture Gamma Emissionmentioning
confidence: 99%